2022
DOI: 10.1080/14479338.2022.2045998
|View full text |Cite
|
Sign up to set email alerts
|

How virtual meetings stimulate process innovations in organisations: mixed-methods evidence from emergency response providers

Abstract: Although meetings are an omnipresent organisational practice for interactive idea generation, we know little about how the switch to digital forms affects innovationoriented behaviours in meetings. This sequential mixed-methods study explores the role of virtual meetings in the generation of process innovations in the Ministry of the Interior of the city-state Hamburg in Germany during the first year of the COVID-19 pandemic. Based on observations, informal interviews, documents, group discussions, and an onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Qin, Yam, Chen, Li and Dong (2021) posited that talking about the COVID-19 pandemic with VT members hurts teams by decreasing team creativity. A different view has been taken by Redlbacher and Hattke (2022) as the authors confirmed through their research that digital meetings have peculiar characteristics, acting as process constraints, which inadvertently facilitates creative collaboration and consequently stimulate innovation. Moreover, Golden (2021) advanced the view that when it comes to the work-family roles, workers could have either a segmentation or integration preference, by the way they separate or combine the two roles.…”
Section: Well-beingmentioning
confidence: 99%
“…Qin, Yam, Chen, Li and Dong (2021) posited that talking about the COVID-19 pandemic with VT members hurts teams by decreasing team creativity. A different view has been taken by Redlbacher and Hattke (2022) as the authors confirmed through their research that digital meetings have peculiar characteristics, acting as process constraints, which inadvertently facilitates creative collaboration and consequently stimulate innovation. Moreover, Golden (2021) advanced the view that when it comes to the work-family roles, workers could have either a segmentation or integration preference, by the way they separate or combine the two roles.…”
Section: Well-beingmentioning
confidence: 99%